Creation of Mayang Village Website Application And Community Empowerment Through Digital Literacy - Nendy Akbar Rozaq Rais; Eko Ari Wibowo; Tino Feri Efendi (JARDIRA – Jurnal Pengabdian Digital dan Rekayasa Informatika, 2025)
BackgroundThe advancement of information and communication technology (ICT) has transformed various aspects of life, including education, the economy, and public transparency. Technology is now an essential part of daily activities. However, in rural areas like Mayang City, digital literacy remains low, limiting the community’s ability to use technology effectively. Although the region has strong human and natural resource potential, many residents—especially those in agriculture and MSMEs—have not yet optimized technology for improving efficiency and welfare. These challenges highlight the need for targeted digital literacy programs and infrastructure support. Contribution: This program contributes to community empowerment by combining digital literacy training with the development of a village website tailored to local needs. It addresses the digital divide in rural areas through practical solutions that strengthen both individual skills and institutional transparency. The approach not only improves access to information and public services, but also builds community capacity to engage with technology sustainably. Method: This activity used a qualitative descriptive approach to examine the digital literacy conditions in Mayang Village. Data were collected through observations and informal interviews. The website development followed the waterfall model, which consists of structured stages: analysis, design, implementation, testing, and maintenance. This method ensured a systematic process suitable for small-scale community-based systems. Results: The program resulted in the development of a village website and a series of digital training sessions for the community. These efforts significantly increased public access to information and reduced dependence on verbal announcements or physical notice boards. The website improved transparency by making government data accessible anytime. The community also became more active in using digital tools for daily tasks, supporting more effective and efficient practices. Conclusion: The integration of digital literacy training and a functional village website has enhanced technological readiness in Mayang Village. It improved information access, governance transparency, and community engagement with technology. This initiative serves as a foundation for future digital transformation in rural areas.